Commodification of Companion Animals in Indonesian Business Law: Regulatory Gaps and an Ecological Justice–Based Reconstruction - Rahmatullah Ayu hasmiati; Mohammed A. Al-Absi (JURNAL AKTA, 2026)
Within Indonesian law, companion animals are predominantly treated as economic objects subject to ownership and commercial exchange. This market-oriented legal construction provides limited recognition of animals as living beings and creates structural weaknesses in the protection of animal welfare, particularly regarding the responsibilities of business actors involved in animal-related activities. This article examines how Indonesian business law constructs the legal status of companion animals and identifies the regulatory gaps affecting the protection of their welfare. The research employs normative juridical (doctrinal) methods using statutory, conceptual, and limited comparative approaches. The study analyzes Article 499 and Article 509 of the Indonesian Civil Code (KUHPerdata), Article 302 of the Criminal Code (KUHP), and Law Number 18 of 2009 as amended by Law Number 41 of 2014 concerning Animal Husbandry and Veterinary Health through the perspective of ecological justice, with a brief comparative reference to South Korean regulatory developments. The findings indicate that Indonesian business law continues to frame companion animals primarily as commodities, resulting in fragmented governance in which welfare protection remains secondary to administrative and economic considerations. The study proposes an ecological justice-based reconstruction that integrates animal welfare obligations into the regulatory governance of companion animal-related businesses through welfare-based licensing, supervisory mechanisms, and duties of care for business actors.